Dietary Intake of Chromista Oil Alters Hepatic Metabolomic Profile of Mice With Excess Fat Mass - Bret M Rust; Forrest H Nielsen; Lin Yan (Nutrition and Metabolic Insights)
Increasing dietary intake of fish oil is frequently recommended for decreasing the risk for cardiovascular diseases and improving metabolic health. We hypothesised that dietary intake of chromista oil (a marine food product and a rich source of long-chain n-3 polyunsaturated fatty acids) ameliorates metabolic impairments in mice with established excess adiposity. Three-to 4-week-old mice (male) were fed a control (n = 12) or a high-fat diet (HFD, n = 24) for 12 weeks to establish body fat mass. Then, mice on the HFD were assigned to 2 groups (n = 12 each) with 1 continuing being fed the HFD and the other fed the HFD with chromista oil for an additional 12 weeks. Intake of chromista oil did not affect body weight and body adiposity of the mice fed the HFD; mice fed the HFD had significantly more body weight and fat mass than control mice. The flattened daily oscillations of respiratory exchange ratio induced by the HFD were not changed by chromista oil intake. Intake of chromista oil significantly increased plasma concentration of insulin, the calculated value of HOMA-IR, and plasma concentration of adiponectin in the mice fed the HFD. However, blood glucose was unaffected by chromista oil. Transcription of genes encoding circadian rhythm and fatty acid metabolism of the 2 HFD-fed groups were similar. Untargeted metabolomic analysis showed that intake of chromista oil altered the hepatic metabolomic profile with substantial alterations in amino acid metabolism. Findings from this study indicate that dietary intake of chromista oil does not improve glucose homeostasis or alter the diminished metabolic flexibility in mice with excess adiposity induced by the HFD. Targeted metabolomic analysis is warranted to investigate the effects of dietary chromista oil, as a source of n-3 poly unsaturated fatty acids, on metabolism in models of obesity.